Sinapic Acid and Sinapate Esters in Brassica: Innate Accumulation, Biosynthesis, Accessibility via Chemical Synthesis or Recovery From Biomass, and Biological Activities - Nguyen, V. P. Thinh; Stewart, Jon D.; Ioannou, Irina; Allais, Florent (Frontiers in Chemistry, 2021)
Sinapic acid (SinA) and corresponding esters are secondary metabolites abundantly found in plants of Brassica family. Belonging to the family of p-hydroxycinnamic acids, SinA and its esters analogues are present in different plant parts and involved in multiple biological processes in planta. Moreover, these metabolites are also found in relatively large quantities in agro-industrial wastes. Nowadays, these metabolites are increasingly drawing attention due to their bioactivities which include antioxidant, anti-microbial, anti-cancer and UV filtering activities. As a result, these metabolites find applications in pharmaceutical, cosmetic and food industries. In this context, this article reviews innate occurrence, biosynthesis, accessibility via chemical synthesis or direct extraction from agro-industrial wastes. Biological activities of SinA and its main corresponding esters will also be discussed.